2019
DOI: 10.1111/jvim.15659
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum iohexol clearance, serum SDMA concentration, and serum creatinine concentration in non‐azotemic dogs

Abstract: Background: Serum creatinine and symmetric dimethylarginine (SDMA) are used as surrogate markers of glomerular filtration rate (GFR) in clinical practice. Data pertaining to the correlations between GFR, SDMA, and serum creatinine in client-owned dogs are limited.Objectives: To describe the relationship between GFR, SDMA, and serum creatinine in a population of client-owned dogs, and to compare clinical utility of SDMA to GFR estimation for detecting pre-azotemic chronic kidney disease.Animals: Medical records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 24 publications
3
33
0
2
Order By: Relevance
“…The type of relationship between the GFR and serum creatinine may have justified the finding of a low number of azotaemic hypothyroid dogs at the time of diagnosis (McKenna et al . 2020). Moreover, endogenous creatinine production seems to be reduced by approximately 33% in dogs with induced hypothyroidism (Panciera & Lefebvre 2009) and this could have mitigate the effect of the decreased GFR on its serum concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The type of relationship between the GFR and serum creatinine may have justified the finding of a low number of azotaemic hypothyroid dogs at the time of diagnosis (McKenna et al . 2020). Moreover, endogenous creatinine production seems to be reduced by approximately 33% in dogs with induced hypothyroidism (Panciera & Lefebvre 2009) and this could have mitigate the effect of the decreased GFR on its serum concentration.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study had described the relationship among GFR, SDMA, and serum creatinine in a population of non‐azotaemic dogs and compared the utility of SDMA to the gold standard of GFR estimation via serum iohexol clearance for the detection of pre‐azotaemic chronic kidney disease (McKenna et al . 2020). SDMA values above the RI of 14 μg/dL were sensitive (90%) but non‐specific (50%) for detection of a ≥40% GFR decrease below the mean GFR of the canine bodyweight category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed increase in SDMA concentration along with the increase in furosemide dosage confirms this hypothesis. The observed correlation between furosemide dosage and SDMA concentration has not been previously reported in dogs and suggests that the administration of diuretics might affect this parameter, as observed for the other kidney function tests [38]. After combining the administration of cardiac therapy and ACVIM staging the analysis yielded no significant effect of these parameters on SDMA concentration.…”
Section: Plos Onementioning
confidence: 44%
“…It is unknown whether the two cats in our study with increased SDMA represent outliers or whether additional studies are needed to reevaluate the normal population‐based RIs for SDMA. A recent study in dogs suggested using a higher cutoff for the upper limit of the population‐based RI for SDMA when evaluating nonazotemic dogs 30 . As with any analyte, it is important to evaluate SDMA in light of the entire clinical picture.…”
Section: Discussionmentioning
confidence: 99%